1999
DOI: 10.1002/(sici)1521-3773(19991018)38:20<2998::aid-anie2998>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in Supercritical Water

Abstract: Water is a special liquid-and not only under "normal" conditions. Water in the supercritical state (shaded area in the phase diagram) is distinguished by special properties which are wholly at variance with those of normal water. So far these have usually been exploited for the purification of waste water, for example for the complete oxidation of poorly degradable substances. But what is the potential of supercritical water for synthesis? Answers are provided here on the basis of thermodynamic and kinetic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
160
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(165 citation statements)
references
References 22 publications
0
160
0
1
Order By: Relevance
“…[3] Bröll et al have briefly reported a base-catalyzed Cannizzaro-type disproportionation of formaldehyde in scH 2 O carried out without a base catalyst. [4] In addition, our in situ Raman spectroscopy measurements have indicated that the extent and strength of hydrogen bonding of scH 2 O are very different to those in heated and ambient H 2 O. [5] This suggests a pronounced stimulation of the breakdown of monomeric water molecules under supercritical conditions, which would account for the acid and base difunctionality of scH 2 O.…”
Section: Structure and Base Catalysis Of Supercriticalmentioning
confidence: 93%
See 1 more Smart Citation
“…[3] Bröll et al have briefly reported a base-catalyzed Cannizzaro-type disproportionation of formaldehyde in scH 2 O carried out without a base catalyst. [4] In addition, our in situ Raman spectroscopy measurements have indicated that the extent and strength of hydrogen bonding of scH 2 O are very different to those in heated and ambient H 2 O. [5] This suggests a pronounced stimulation of the breakdown of monomeric water molecules under supercritical conditions, which would account for the acid and base difunctionality of scH 2 O.…”
Section: Structure and Base Catalysis Of Supercriticalmentioning
confidence: 93%
“…[2] The understanding of the structure and the reactivity of silylnickel species [3] is indispensable for the development of new catalytic methodologies. Although a number of mononuclear silylmetal complexes are known for all Group 10 metals, structurally characterized silylene-bridged dinuclear complexes have been reported only for platinum [4] and palladium. [5,6] These dinuclear species are considered to play important roles in catalytic processes.…”
Section: Methodsmentioning
confidence: 99%
“…Above the critical temperature, the rate constant increases more rapidly with temperature than that with temperature under the critical temperature. This indicates that chlorobenzene can be completely dissolved in supercritical water, which eliminates mass-transfer limitations and permits the dechlorination to proceed at a faster rate (Broll et al 1999). The Arrhenius law with activation energy of 23.2 ± 2.3 kJ mol -1 roughly obeys in subcritical water (Wei et al 2009).…”
Section: Effect Of Residence Time and Temperature On Reductive Dechlomentioning
confidence: 90%
“…They reported that in the supercritical treatment the methanol acts not only as a reactant but also as an acid catalyst. The ionic product, which is an important property in chemical reactions, can be also improved by increasing the pressure [13]. If the reaction mixture becomes more acidic, the reaction rate will be improved.…”
Section: Discussionmentioning
confidence: 99%